RANCANG BANGUN ALAT CUCI TANGAN OTOMATIS BERBASIS ARDUINO UNTUK MENCEGAH PENYEBARAN COVID-19 - wahyu woro lestari; Yuana, Haris; Kirom, Sabitul (JATI (Jurnal Mahasiswa Teknik Informatika), 2022)
Automatic hand washing tools based arduino are hand washing tools that have automatic hand soap and automatic water faucets with sensitivity from ultrasonic sensors. By using this hand washing tool, the user of the tool does not need to hold it. This research was conducted in Keningaran Village, Kel. Bajang, Kec. Talun, Kab. Blitar to tackle the spread of Covid-19 which is spreading among the people in Kab. Blitar. This research uses the method of development or Research and Development. (RnD) The purpose of this research is (1) to find out how to make an Arduino-Based Automatic Handwashing Design, and (2) to see the feasibility of testing the Arduino-Based Automatic Handwashing Tool. The results of this study are (1) there are eleven steps to designing an Arduino-based hand washing device and (2) testing hand washing tools from the program to the final manufacture of the tool must be done several times until the tool runs according to what the author wants to test the feasibility of hand washing tools.